2004
DOI: 10.1542/peds.113.4.e365
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Infarction in Adolescent Males Associated With Acute Marijuana Use

Abstract: ABSTRACT.Objective. To demonstrate the clinical characteristics, radiologic findings, and neuropathological features of tetrahydrocannabinol-related posterior fossa ischemic stroke in adolescent patients.Design. A retrospective case and chart review of 3 cases encountered at a tertiary care institution over a span of 5 years.Setting. Inpatient and intensive care hospitalization units managing children and adolescents.Subjects. Male adolescent patients with ischemic cerebellar stroke after use of marijuana.Diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 20 publications
4
31
1
Order By: Relevance
“…The attenuated decreases in DV with MP in the marijuana abusers were observed throughout the brain but were most accentuated in cerebellum. The higher sensitivity of the cerebellum to what we interpret to reflect changes in vascular reactivity with marijuana abuse is consistent with clinical findings that report strokes associated with marijuana abuse are more frequently localized in the posterior circulation and ischemia is most frequently observed in cerebellum (25,(54)(55)(56). Cerebellar arteries express CB1 receptors in the smooth muscle layer (57), but because comparisons with arteries in other brain regions have not been done, it is not possible to determine if higher levels of CB1 receptors in cerebellar arteries underlie their higher sensitivity to vascular effects from marijuana.…”
Section: Mp-induced Changes In DVsupporting
confidence: 90%
“…The attenuated decreases in DV with MP in the marijuana abusers were observed throughout the brain but were most accentuated in cerebellum. The higher sensitivity of the cerebellum to what we interpret to reflect changes in vascular reactivity with marijuana abuse is consistent with clinical findings that report strokes associated with marijuana abuse are more frequently localized in the posterior circulation and ischemia is most frequently observed in cerebellum (25,(54)(55)(56). Cerebellar arteries express CB1 receptors in the smooth muscle layer (57), but because comparisons with arteries in other brain regions have not been done, it is not possible to determine if higher levels of CB1 receptors in cerebellar arteries underlie their higher sensitivity to vascular effects from marijuana.…”
Section: Mp-induced Changes In DVsupporting
confidence: 90%
“…Others might be systemic hypotension, instable cerebral autoregulation, instable cerebral blood flow, vacuities, cerebral vasoconstriction syndrome, and cardiac embolism with atrial fibrillation. [2,3,7,8,10] Although a few of these mechanisms may coexist, evidence explaining the causes of stroke needs to be found.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, marijuana abuse causes systemic hypertension and damage of vasomotor reflexes and the central nervous system. [10,13] Geller et al [3] reported three cases of cerebellar infarction caused by marijuana abuse. Cerebellar infarction was found by biopsy or necropsy and infi ltration of infl ammatory cells was detected in the cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations